The Teachers' Readiness and Administrators' Support for the Implementation of Performance-Based Assessments in the K to 12 - Clark Dominic Alipasa (Philippine Association of Institutions for Research, Inc., 2021)
Performance-based assessments are designed by schools to measure what the learners know and can do in diverse ways. According to the Department of Education, these assessments should enable the students to integrate their 21st-century skills and their knowledge, understanding, values, and attitudes in specific real-life situations. To determine the extent of the teachers' readiness for the implementation and the extent of support provided by the administrators in terms of supervision and assistance and the administrators' coaching and mentoring, expert-validated questionnaire checklists were administered to 65 teachers in the Senior High School. Findings show that the extent of the teachers' readiness to implement performance-based assessment is the extent. In contrast, the extent of the administrators' support in terms of administration and supervision and coaching and mentoring are very great. The teachers' readiness has been attributed to their field studies, professional education subjects, and practice teaching wherein they observed and experienced designing performance assessments. Also, the administrators supervised and assisted the teachers by allowing them to create their assessments, providing suggestions, and encouraging participation. To further the implementation, enriched training and workshop sessions, maintaining the communication among the teachers and administrators, and giving credit, independence, and commendations to the faculty members are recommended.